THE EFFORTS TO IMPROVE THE LEARNING MOTIVATION BY USING DISCUSSION METHODS IN MATHEMATICS FOR VII GRADE STUDENTS - Diah Trie Wahyuni; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The learning method that is less interesting in the Mathematics subject makes the low studentâ€™s motivation to learn Mathematics. This research aims to improve studentâ€™s motivation in Mathematics subject by using the discussion method for VII grade students â€œAâ€ of Muhammadiyah Pakem Junior High School (SMP Muhammadiyah Pakem) at even semester in Sleman districts academic year 2016/2017. This research is Classroom Action Research (CAR). The subject is the seven grades students "A" of Muhammadiyah Pakem Junior High School, and the object is studentâ€™s learning motivation after the implementation of the discussion method in Mathematics subject. The data collection technique uses observation, tests, and questionnaires. The data analysis uses descriptive qualitative and quantitative analysis. The research is conducted in two sessions, where each session consists of two meetings. The session was stopped after the result of the indicator was reached out to a minimum of 60% or good criteria. The results show that the discussion method can improve the learning motivation in Mathematics subject for VII grade students "A" of Muhammadiyah Pakem Junior High School in Sleman at even semester of academic year 2016/2017. It is shown based on the observation result from each session. The first session is 56,025% with sufficient criteria, and the second session increase becoming 72,631% with good criteria. At the same time, the test result of learning shows that the first session is 57,368, and the second session gets 72,631. Then, the questionnaires' results for the student's learning motivation show that the first session gets 57.906% with sufficient criteria, and the second session increases, becoming 73.867% with good criteria.